Rewetting drained boreal peatland forests does not mitigate climate warming in the twenty-first century - Launiainen, Samuli; Ahtikoski, Anssi; Rinne, Janne; Ojanen, Paavo; Hökkä, Hannu (Springer, 2025)
Rewetting drained peatland forests restores pristine ecosystem functions, improves peatland ecological status, and has been considered to mitigate climate change. We quantified climate impact of rewetting boreal peatland forests in Northern Europe by comparing the radiative forcing of alternative restoration pathways to that of continued forestry use. We considered changes in soil carbon dioxide, methane and nitrous oxide balance, tree stand carbon sink-source dynamics, albedo change, and included the wood product carbon storage and release. We show that restoring nutrient-rich drained boreal peatland forests contributes to climate warming in the short and medium term (< 200 yr), except in specific cases when tree stand carbon storage is preserved. Rewetting nutrient-poor peatland forests has a persistent warming impact. Our results indicate the ecological benefits of rewetting drained boreal peatland forests come at a climate cost, and that restoration is unlikely to mitigate climate change within a timeframe relevant to the EU climate goals.
Keywords: Climate change mitigation; Forest peatland restoration; Greenhouse-gas balance; Radiative forcing; rewetting